2016
DOI: 10.1016/j.jpag.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with Classical Polycystic Ovary Syndrome Have Alterations in the Surrogate Markers of Cardiovascular Disease but Not in the Endothelial Function. The Possible Benefits of Metformin

Abstract: Study Objective To study whether adolescents with the classical form of polycystic ovary syndrome have alterations in metabolic and vascular structure and function. The effect of metformin was evaluated. Design Controlled study Setting University outpatient clinic Participants Eighteen PCOS non obese adolescents were enrolled. Seventeen healthy age-matched adolescents were recruited as controls. Interventions The metabolic profile and the endothelial structure and function were evaluated. Main Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 40 publications
(49 reference statements)
1
22
0
1
Order By: Relevance
“…PCOS may also be associated with increased incidence of cardiovascular disease and this risk should be considered even in young women with PCOS [11]. Surrogate markers of cardiovascular disease are already altered in adolescent PCOS ladies and metformin treatment positively modified these markers leading to the proposal of a preventive treatment [12]. However, the impairment of Hcy metabolism resulting from metformin treatment [5,6] may lead to the opposite long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…PCOS may also be associated with increased incidence of cardiovascular disease and this risk should be considered even in young women with PCOS [11]. Surrogate markers of cardiovascular disease are already altered in adolescent PCOS ladies and metformin treatment positively modified these markers leading to the proposal of a preventive treatment [12]. However, the impairment of Hcy metabolism resulting from metformin treatment [5,6] may lead to the opposite long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Radial and aortic augmentation indices were found to be similar between PCOS and non‐PCOS patients. FMD has been found to be similar between PCOS and non‐PCOS groups in some studies; however, increased FMD was also reported in a PCOS group in another study . Serum testosterone levels were higher in the PCOS groups in some of these studies and free androgen index was higher in others when compared to controls.…”
Section: Discussionmentioning
confidence: 78%
“…Endotelial dysfunction has been investigated in PCOS patients using different methods. Although some studies have not shown any differences between PCOS and non‐PCOS women using central and peripheral pulse wave velocities, others have reported differences . Radial and aortic augmentation indices were found to be similar between PCOS and non‐PCOS patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The possibility of making the diagnosis of PCOS is controversial if a patient is adolescent. In fact, the same criteria (anovulation, hyperandrogenism, and polycystic ovaries) that are used for the diagnosis in adults, in adolescents may be transitory or within evolution [22].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%